Environmental DNA survey to detect an endemic cryptic fish, Anablepsoides cryptocallus, in tropical freshwater streams. Issue 3 (13th January 2023) - Baudry, Thomas; Mauvisseau, Quentin; Arqué, Alexandre; Goût, Jean‐Pierre; Delaunay, Carine; de Boer, Hugo J.; Grandjean, Frédéric
Abstract: Martinique island is a biodiversity hotspot in the Lesser Antilles that harbours many endemic species. One of these, Anablepsoides cryptocallus, also known as 'Poisson gale', is the only endemic freshwater fish of Martinique and a species with a poorly understood distribution range. In this study, an environmental DNA (eDNA) detection protocol was developed, validated, and optimized, targeting a short fragment (125 bp) of the A. cryptocallus COI mitochondrial gene, to investigate the presence of this species in Martinique. Fifty‐seven sites spread over 43 permanent rivers and two wetlands were sampled using both eDNA and conventional fishing (dip net capture). Presence was confirmed in 27 sites using eDNA detection, and in nine sites by dip net fishing. eDNA‐based detection of A. cryptocallus was effective and less time‐consuming than conventional fishing, making it a relevant tool for future studies throughout the island. Even though A. cryptocallus was found to be present in a significant number of sites, many sites previously known for this species were found to be negative, highlighting the need for continuous monitoring. There is now an urgent need to propose protection status for this endemic species to preserve its preferential habitats, as these are being increasingly threatened by human activities that are leading to habitat loss and fragmentation.